Decorated marines of the Fourth Brigade in World War I - Clark, George B. (McFarland, 2007)
"Lists each individual and the honors he received. Citations, which were generally written by a superior, as originally written. Prewar and postwar experience is noted. The award entry site is also listed. Foreign honors are denoted when applicable. An appendix contains detailed information on the inauguration of the Silver Star citation"--Provided by publisher.
"Lists each individual and the honors he received. Citations, which were generally written by a superior, as originally written. Prewar and postwar experience is noted. The award entry site is also listed. Foreign honors are denoted when applicable. An appendix contains detailed information on the inauguration of the Silver Star citation"--Provided by publisher.
Includes bibliographical references (p. 249-251) and index
Keywords: United States -- Marine Corps -- Medals, badges, decorations, etc; United States -- Marine Corps -- Marine Brigade, 4th; United States -- Marine Corps -- Registers; USA -- Marine Corps; Weltkrieg (1914-1918); World War, 1914-1918 -- Medals -- United States; World War, 1914-1918 -- Registers; Orden -- Ehrenzeichen; Erster Weltkrieg; USA